Evaluasi Pembelajaran daring Berbasis Google Classroom di SMAN 1 Kubu, Kecamatan Kubu, Kabupaten Karangasem - Widita, Putu Oxin Oktarina; Sujana, I Nyoman (Universitas Pendidikan Ganesha, 2023)
The purpose of this study is to find out the effectiveness of online learning based on Google Classroom in SMAN 1 Kubu, Kubu District, Karangasem Regency is reviewed from the dimensions of context, input, process and product. This study uses evaluative research design with a quantitative approach. The population in this study is all teachers in SMAN 1 Kubu which amounts to 43 people. The sampling technique used is a jenuh sampling technique. The data collection method uses questionnaires and documentation analyzed using the Z-score and T-score descriptive tests and then the analysis results are converted in the Prototype Glickman quadrant. The results of this study showed that in the context dimensions are positive (+), inputs are negative (-), processes are positive (+), and products are positive (+). The results showed that the evaluation of Online learning based on Google Classroom in SMAN 1 Kubu, Kubu District, Karangasem Regency was categorized as quite effective.